A cross-sectional and prospective analyse of reallocating sedentary time to physical activity on children's cardiorespiratory fitness. Issue 15 (3rd August 2018) - Santos, Diana A.; Marques, Adilson; Minderico, Cláudia S.; Ekelund, Ulf; Sardinha, Luís B.
ABSTRACT: Cardiorespiratory fitness (CRF) is associated with health benefits in children, improving cardiac morphology, cardiovascular disease risk factors, and biological outcomes. This study aimed to examine the substitution effects of displaying a fixed duration of sedentary time with a fixed duration of physical activity (PA) at different intensities on children's CRF. A total of 315 children (136 boys) were assessed (age: 10.6 ± 0.6 years old). Outcomes at baseline and follow-up (16-months) were CRF determined using a maximal cycle test and sedentary time and PA measured with accelerometers. Data were analysed by isotemporal substitution analyses estimating the effect of reallocating 30 min/day of sedentary time by light (LPA), moderate (MPA) and vigorous physical activity (VPA) on CRF. VPA was positively and significantly associated with CRF cross-sectional (β = 0.026, p < 0.001) and prospectively (β = 0.010, p < 0.001). Reallocating 30 min/day of sedentary time into VPA was positively cross-sectionally (β = 0.780, p < 0.001) and prospectively (β = 0.303, p < 0.05) associated with CRF. Conversely, relocating 30-minutes of sedentary time into 30 minutes of LPA and MPA was not associated with CRF. These results suggest that reallocating an equal amount of time from sedentary into VPA is cross-sectional and prospectively associated with a favourable CRF.